A dominant spotted leaf gene TaSpl1 activates endocytosis and defense-related genes causing cell death in the absence of dominant inhibitors. (September 2021) - Zhang, Hong; Xu, Xiaomin; Wang, Mengmeng; Wang, Hui; Deng, Pingchuan; Zhang, Yaoyuan; Wang, Yanzhen; Wang, Changyou; Wang, Yajuan; Ji, Wanquan
Highlights: TaSpl1, a dominant gene, was usually suppressed by dominant-negative regulators. TaSpl1 simulated a regulated cell death phenotype in the absence of pathogen. TaSpl1 activated defense genes that enhance Pst and Bgt resistance in adult plants. Abstract: The spotted leaf lesion mimic trait simulates cell death in a plant responding to pathogen infection. Some spotted leaf genes are recessive, while others are dominant. A small number of plants with a lesion mimic phenotype appeared in a segregating population obtained by crossing two normal green wheat strains, XN509 and N07216. Here, we clarified the genetic model and its breeding value. Phenotyping of the consecutive progeny populations over six cropping seasons showed that the spotted leaf lesion mimic phenotype was controlled by a dominant gene designated TaSpl1, which was inhibited by two other dominant genes, designated TaSpl1-I1 and TaSpl1-I2 . Using bulked segregant analysis RNA-seq (BSR-Seq) and newly developed KASP-PCR markers, the TaSpl1 and TaSpl1-I1 loci in N07216 were mapped to the end of chromosomes 3DS and 3BS, respectively. Plants with the spotted phenotype showed lower levels of stripe rust and powdery mildew than those with the normal green phenotype. Compared with normal leaves, the differentially expressed genes in spotted leaves were significantly enriched in plant-pathogen interaction and endocytosis pathways. There were no differences in the yield parameters of the F5 and F6 sister lines, N13039S with TaSpl1 and N13039 N without TaSpl1 . These results provide a greater understanding of spotted leaf phenotyping and the breeding value of the lesion mimic allele in developing disease-resistance varieties.